PENGEMBANGAN MEDIA PEMBELAJARAN SCRAPBOOK UNTUK MENINGKATKAN KETERAMPILAN MEMBACA SISWA KELAS II SEKOLAH DASAR - Oktaviani, Ursula Dwi; Kurniati, Agusta; Yuniki, Yuniki (STKIP Persada Khatulistiwa Sintang, 2024)
This research aims to describe the development of scrapbook learning media to improve the reading skills of second grade elementary school students. The research was carried out using the ADDIE Research and Development model, with stages of analysis, design, development, implementation and evaluation. The sampling technique was purposive sampling with a total of 63 students. Data collection tools include observation, questionnaires, test questions, and documentation. The trial design uses one group pretest-posttest design. The test subjects were classes IIA, IIB and IIC at SDN 12 Jerora Sintang. The results of media development research and the results of students' reading skills are as follows. (1) The feasibility of the media by media experts was 97% and 93% by material experts was declared to be very feasible criteria and worthy of being tested on students. (2) The results of small group students' reading skills in the pretest class IIB were 23% while the posttest was 86% and in the large group trial in the pretest class IIA 32% while the posttest was 86%, then the pretest class IIC was 27% while the posttest was 82%, from the data the results were obtained. students' reading skills improved significantly. (3) The response of the small group of students in class IIB was 89%, while the large group in class IIA was 93% and in class IIC 92% was categorized as very good.